The Contribution of Compassion Assisted Projects Towards Psycho-Social Welbeing of OVC in Mbale District - Yunus Abby Zalika (Uganda Christian University, 2024)
Compassion is being a Christian child development ministry that is motivated by faith to assist children and their families who are living in poverty regardless of their beliefs, gender or background. Holistic child development that takes a child through a process of growth and fulfilment in all dimensions of their life: spiritually, economically, socio-emotionally and physically. This study was carried out in Mbale District and was guide by the following objectives, finding out the role of Compassion assisted Projects towards Psychosocial Wellbeing of OVC, investigating into the relevance of Compassion assisted Projects towards Psychosocial Wellbeing of OVC and assessing on the impact of Compassion assisted Projects towards Psychosocial Wellbeing of OVC in Mbale District. A descriptive survey design was used since the sample size was quite large. This survey design was used to gather information from across sector of respondents at a single point in time as the design therefore put into consideration at all steps involved concerning the assessment of compassion assisted projects towards health, education and skills improvement of children and caretakers in Mbale District. Quantitatively, the researcher employed the questionnaires in the data collection from across sections of respondents and qualitatively, she also equally employ documentation and interview schedules to get both primary and secondary data. The sample size was derived from the population of 120 beneficiaries, using a confidence interval of 95% and margin of error of 0.5% as described and a sample of 93 respondents were obtained. The findings of this study were that, In Uganda, International child sponsorship is offered in various ways by a large number of NGOs as a means to alleviate child poverty. While the sponsoring of individual children has been criticized for its divisive effects, furthermore, Children have gained skills in vocational related courses through which are able to support their families especially their siblings, for example, courses in brick laying and making these Children have been also able to reach their dream goal as they have attained many professions at different levels of education including certificates, diplomas, degrees among others and they have become self-sustaining. However, the research also recommends that, it is important for compassion project management team to strengthen its monitoring and evaluation systems through internal controls, internal audits particularly on the areas of health, to make sure that the children and caregivers receive health services from qualified personnel
Undergraduate Research